Evaluating the Effects of Different Doses of Vitamin B2 and Single Dose of Vitamin B12 Against Myelosuppression Induced by Cyclophosphamide in Experimental Rats - Ghanim, Waleed K.; N. Al-Shawi, nada (Iraqi Journal of Pharmaceutical Sciences, 2020)
Cyclophosphamide is chemotherapeutic agent that utilized for the treatment of different malignancies; however its’ used associated with numerous adverse effects. Vitamin B2 and vitamin B12 suggested having myeloprotective effect. This work is designed to investigate the myeloprotective effect of both vitamins against cyclophosphamide induced myelosuppression. One hundred adult rats of both sexes were used in this study. The animals were randomly enrolled into ten groups of 10 rats each. Group I: Control group. Group II: Cyclophosphamide-treated. Group III and Group IV Orally-administered vitamin B2 (10, and 40 mg/kg/day), respectively alone for 7 days. Group V: Orally-administered vitamin B12 (0.1 mg/kg/day) alone for 7 days. Group VI and Group VII: Orally-administered vitamin B2 (10, and 40 mg/kg/day), respectively for 7 days and a single IP injection of cyclophosphamide (150 mg/kg) at day 7.Group VIII: Orally-administered vitamin B12 (0.1 mg/kg/day) for 7 days and a single IP injection of cyclophosphamide (150 mg/kg) at day 7. Group IX: Orally-administered a combination of vitamin B2 (10 mg/kg/day) and vitamin B12 (0.1 mg/kg/day) for 7 days and a single IP injection of cyclophosphamide (150 mg/kg) at day 7. Group X: orally-administered a combination of vitamin B2 (40 mg/kg/day) and vitamin B12 (0.1 mg/kg/day) for 7 days and a single IP injection of cyclophosphamide (150 mg/kg) at day 7. On day eight, animals were sacrificed and blood collected for CBCs and femur bone were extracted for bone marrow histological examination. Vitamin B2 and vitamin B12 significantly (P<0.05) increase CBCs; and the combination of vitamins produce -a significant (P<0.05) increase in CBCs compared to corresponding counts in other Groups, and -improve histopathological changes compared to Group II rats. In conclusion both vitamins may have myeloprotective effects against cyclophosphamide-induced myelosuppression.